1982
DOI: 10.3109/00016348209156552
|View full text |Cite
|
Sign up to set email alerts
|

Hydrops Fetalis Caused by Maternal Indomethacin Treatment

Abstract: Hydrops fetalis was diagnosed in one of two twins, while the other suffered from cardiac failure. Indomethacin administered to the mother to arrest premature labor, seemed to be the predisposing factor resulting in the hydrops fetalis. The possible relationship between intrauterine closure of the ductus arteriosus and the pathogenesis of hydrops fetalis is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

1990
1990
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Maternal side effects include the prolongation of pregnancy and labor [6,7]. Reported adverse fetal side effects of indomethacin and other NSAIDs include constricted ductus arteriosus (DA) [3,[8][9][10][11][12], limb ischemia [13], hydrops fetalis [14,15], oligohydramnios, ileal perforation [16], and cystic brain lesions [17]. The possible teratogenic effects of NSAIDs used in early pregnancy include gastroschisis, associated with aspirin and ibuprofen [3,11].…”
Section: Introductionmentioning
confidence: 99%
“…Maternal side effects include the prolongation of pregnancy and labor [6,7]. Reported adverse fetal side effects of indomethacin and other NSAIDs include constricted ductus arteriosus (DA) [3,[8][9][10][11][12], limb ischemia [13], hydrops fetalis [14,15], oligohydramnios, ileal perforation [16], and cystic brain lesions [17]. The possible teratogenic effects of NSAIDs used in early pregnancy include gastroschisis, associated with aspirin and ibuprofen [3,11].…”
Section: Introductionmentioning
confidence: 99%
“…Maternal administration of the prostaglandin synthe tase inhibitor indomethacin may lead to constriction of the fetal ductus arteriosus resulting in increased blood flow through the pulmonary bed, fetal pulmonary arterial hypertension, right ventricular overload, severe right heart changes, and congestive heart failure [5,[19][20][21][22], Constrictive effects of glucocorticoids on the ductus arter iosus have also been described [23], The prenatal diagno sis of indomethacin-induced constriction is based on increased ductal peak systolic and diastolic flow velocities of > 1.4 and >0.3 m/s, respectively [24], and a low pulsatility index (mean ± 2 SD: 1.25 ± 0.76) [10], There are only sporadic reports of idiopathic prema ture stenosis or closure of the ductus arteriosus. Pathologi cal examinations have demonstrated right atrial and ven tricular dilatation, definite signs of decompensated con gestive heart failure, and hydrops fetalis associated with idiopathic premature stenosis or closure of the ductus arteriosus with internal ductal diameters ranging from 0.0 to 2.0 mm [1][2][3][4][5][6].…”
Section: Discussionmentioning
confidence: 99%
“…Siu and Lee [23] reported severe pulmonary hypertension and temporary hypertrophic cardiomyopathy on the right side of the heart in newborn rats as a result of early closure of the DA following shortterm maternal exposure to DS. Some studies have reported that NSAIDs cause teratogenic side effects in the fetus, such as contraction of the DA, ischemia of the extremities, oligohydramnios, hydrops fetalis, cystic brain lesions, and ileal perforation [24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%